2020
DOI: 10.1039/d0fo02017f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activities of marine sulfated polysaccharides against SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread around the world at an unprecedented rate. In the present study, 4 marine sulfated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 21 publications
(27 reference statements)
5
127
0
2
Order By: Relevance
“…reacts with the Plpro protein [183]. Sulphated polysaccharides from marine microorganisms like sea cucumber Stichopus japonicus and Fucoidan from brown algae can have an excellent inhibitory effect on SARS-CoV-2 [184]. Recent reports revealed a T3 terpenoid isolated from marine sponge Cacospongia mycofinensis inhibits the action of Mpro via hydrogen bond interactions [185].…”
Section: Microbial Metabolites and Compounds From Marine Microorganisms Targeted Against Sars-cov-2mentioning
confidence: 99%
“…reacts with the Plpro protein [183]. Sulphated polysaccharides from marine microorganisms like sea cucumber Stichopus japonicus and Fucoidan from brown algae can have an excellent inhibitory effect on SARS-CoV-2 [184]. Recent reports revealed a T3 terpenoid isolated from marine sponge Cacospongia mycofinensis inhibits the action of Mpro via hydrogen bond interactions [185].…”
Section: Microbial Metabolites and Compounds From Marine Microorganisms Targeted Against Sars-cov-2mentioning
confidence: 99%
“…This suggests that the fucoidan can potentially inactivate the virus by direct contact [36]. Recently, in vitro tests with two fucoidans extracted from the edible brown algae showed the molecules to be potent inhibitors of SARS-CoV-2 [37]. Crucially, fucoidans clearly outcompeted Remdesivir, which is currently approved for emergency use for severe COVID-19 infections [38].…”
Section: Fucoidansmentioning
confidence: 99%
“…This is done by describing a method of extraction of the particular extract or molecule, describing its antiviral effect against a particular virus or a group of viruses, and/or by presenting the detailed composition of a compound, including algae-derived substances, with antiviral potential. A considerable number of patents (37) protect not only the method for antiviral production but its method of application as well. The remaining five patents focus only on a method for antiviral use.…”
Section: Patent Analysismentioning
confidence: 99%
“…People showed that marine polysaccharide may inhibit SARS-Cov-2 infection (Song S, et al 2020), however the convinced targeting molecule and mechanism are still unknown. SARS-CoV-2 includes two open reading frames ORF1a and ORF1b (Yin et al, 2020).…”
Section: Crude Polysaccharide 375 Was a Potent Inhibitor Of Sars-cov-mentioning
confidence: 99%